Constitutional Safeguard for Preservation of Democratic Political Culture and the Legitimacy of Political Porting in Nigeria - Godspower Ehirim, Ugochukwu; Bernice Ohwomeregwa, Ogechi; Flora Ehirim, Nwanneka; Koiki-Owoyele, Adeyinka (Udayana Journal of Law and Culture, 2025)
Political parties are the mainstay of democratic governance, critical to policy formulation and to sustain of political structure in modern states. They are driven by entrenched ideologies besides their focus on attaining economic and political powers. Political porting one of the trending epithets for cross-carpeting, has become too frequent a phenomenon as to be capable of torpedoing Nigeria’s nascent democracy. The resurgence of this ugly tend and the near-anarchy situation in Rivers State of Nigeria has reignited the arguments around the legitimacy of this political culture. This article examines the constitutional enactments and judicial authorities as they impact on the choice of an elected political office holder to defect to another political party while still holding office. It also situates Nigeria’s democracy within international norm which should interest the universal institutions to support. Adopting the doctrinal research method, the article reveals the inadequacy of the anti-defection provisions of the laws in Nigeria as well as the weakness of the judiciary to rise to the occasion. The article recommends law reforms as well as a clear-cut ideology for political parties to guarantee the survival of democracy in Nigeria.